The effect of growth medium on an Escherichia coli pathway mirrored into GC/MS profiles. (7th September 2017) - Ratiu, Ileana-Andreea; Ligor, Tomasz; Bocos-Bintintan, Victor; Al-Suod, Hossam; Kowalkowski, Tomasz; Rafińska, Katarzyna; Buszewski, Bogusław
Abstract: Escherichia coli ( E. coli ) is a Gram-negative coliform bacterium that is commonly found in the lower intestine of warm-blooded organisms. Most of the strains are harmless but some serotypes are pathogenic, meaning they can cause illness, either diarrhea or illness outside the intestinal tract. The aim of this work is to assess which components are generated for the purpose of E. coli target analysis. In this study, we intend to emphasize the importance of cultivability and to prove that growth media plays a crucial role in bacteria growth. To do this, E. coli was cultivated in three different growth mediums: (a) trypcase soy broth (TSB), (b) Mueller Hinton (MH), and (c) minimal salts (M9) enriched with glucose, respectively. Solid phase micro extraction was used as a sampling method, followed by gas chromatography–mass spectrometry for subsequent analysis. The relevant microbial volatile organic compounds (MVOCs) released in the headspace over the cultures of the E. coli bacteria and the afferent metabolic processes that occur in order to generate these compounds are presented in this work. The characteristic volatile compounds found in E. coli strain emissions were indole, phenylethyl alcohol and a series of esters when it was grown in TSB. Different pyrazines were found (pyrazine, 2-ethyl-3, 5-dimethyl-, pyrazine, 2, 5-dimethyl- and pyrazine, trimethyl-) when it was cultivated in MH. Long-chain alcohols such as 2-pentadecanol, 9-tetradecen-1-ol and 11-hexadecenol occurred in M9. Dimethyl disulfide, dimethyl trisulfide and a consistent number of alcohols and ketones were observed for E. coli cultivated in all three growth mediums. The occurrence and biosynthesis of these MVOCs clearly denote that the growth media used plays a crucial role in bacterial cultivation. The biomarker chemicals documented from this work may ultimately be used to identify bacterial infections by analyzing exhaled breath.